Tuberculous Lymphadenopathy Mimicking Pancreatic Neoplasm - Kunikazu Hoshino; Shingo Arakaki; Daisuke Shibata; Tatsuji Maeshiro; Akira Hokama; Fukunori Kinjo; Masayuki Shiraishi; Tadashi Nishimaki; Jiro Fujita (Case Reports in Medicine)
Abdominal tuberculosis (TB) is the sixth most common location of extrapulmonary TB involvement. Because its symptoms and signs are often nonspecific, laboratory and imaging findings mimic other diseases including carcinoma. Therefore, the diagnosis of abdominal TB is challenging. We herein report a case of 74-year-old woman who presented with abdominal pain, anorexia, and weight loss. She had been given a diagnosis of pancreatic head carcinoma. Laboratory data was unremarkable except for elevated erythrocyte sedimentation rate, CA125, and sIL-2R. CT scan revealed multiple enlarged peripancreatic lymph nodes and concentric thickening of the ileocecal wall. Colonoscopy demonstrated deformed ileocecal valve and erosions. Histological examination showed epithelioid granulomas. Laparoscopy revealed numerous white tubercles diffusely covering the parietal peritoneum. Histopathological images of peripancreatic lymph node revealed large multiple caseating granulomas surrounded by Langhans_giant cells and epithelioid cells. Polymerase chain reaction and culture of the specimens were positive for Mycobacterium tuberculosis. Tuberculous lymphadenopathy, colitis, and peritonitis were finally diagnosed. She responded well to the antitubercular treatment.